Clinical Characteristics of the Premature Ejaculation Sufferers in Aegean Region of the Turkey: A Multicentre, Observational Study - Ahmet Cihan; Ömer Demir; Ali Şahin; Fatih Zeren; Deniz Bolat; Burak Özçift; Abdulkadir Pektaş; Ertan Can; Bilal Gümüş; Tahir Turan; Ahmet Bölükbaşı; Haluk Erol; et al. (Journal of Urological Surgery)
Demonstration of the intra-vaginal ejaculation latency time (IELT) distribution in male subjects and its clinical expressions among couples in the Aegean region of the Turkey. Materials and Methods Subjects were recruited to the study from six different urologic centers in the Aegean region. During the enrollment period subjects were recruited in to two group according to presence of premature ejaculation (PE). PE diagnosis was made according to DSM-4 definition. Subjects and their partners were evaluated with patient reported outcome measures (PRO) related to the ejaculation-based questionnaire (Premature ejaculation patient profile questionnaire -PEPQ). Stopwatch measurements were also asked from each couple to record intravaginal ejaculation latency time (IELT). Couples who completed two clinical visits with 4 wk interval were recruited to the data analysis. Results Among 141 eligible subjects, mean age was 36.5±9.7 years and mean partner age was 32.9±9.8 years. Following the initial evaluation 80 subjects recruited to group 1(PE) and 41 subjects recruited to the group 2 (non-PE). Geometric mean IELT of the subjects was significantly differed between PE and non- PE group (64.7±66.8 vs. 521.5±414.7 seconds, p<0.001). All of the PEPQ domain scores were also differed between groups. Subjects in the PE group gave poor ratings than non-PE subjects. Partner responses were similar pattern. Correlation analyses of the PEPQ scores demonstrated significant positive correlations between “perceived control over ejaculation” and “satisfaction with sexual intercourse” domains of the PEPQ and with IELT. Conclusion Geographic distribution of IELT and its impacts among couples by the several subjective aspects of PRO measures should be assessed during PE investigation